2014
DOI: 10.1073/pnas.1416079111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of long-lived proteins retained in cells undergoing repeated asymmetric divisions

Abstract: Long-lived proteins have been implicated in age-associated decline in metazoa, but they have only been identified in extracellular matrices or postmitotic cells. However, the aging process also occurs in dividing cells undergoing repeated asymmetric divisions. It was not clear whether long-lived proteins exist in asymmetrically dividing cells or whether they are involved in aging. Here we identify long-lived proteins in dividing cells during aging using the budding yeast, Saccharomyces cerevisiae. Yeast mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 81 publications
4
84
1
Order By: Relevance
“…Thayer et al (35) recently used isotope labeling and total proteome MS to identify long-lived asymmetrically retained proteins (LARPs). They identified several full-length proteins (Mrh1, Pma1, Sur7, Thr1, and Hsp26) and many protein fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Thayer et al (35) recently used isotope labeling and total proteome MS to identify long-lived asymmetrically retained proteins (LARPs). They identified several full-length proteins (Mrh1, Pma1, Sur7, Thr1, and Hsp26) and many protein fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Even at the superficial descriptive level, single-cell RNA-seq cannot capture post-translational modifications (PTMs). Well-characterized regulatory mechanisms, such as long-lived proteins [23] and translational regulation [24] make mRNAs poor surrogates for functional proteins. Munsky et al [25] simulated the distributions of mRNA and protein levels for a number of gene regulatory motifs, and showed that depending on the motif, mRNA levels were not necessarily correlated to the corresponding protein’s level.…”
Section: New Technology Can Enable New Biologymentioning
confidence: 99%
“…Pma1 is an ATP-dependent proton pump that generates the essential pH gradient across the plasma membrane, consuming as much as 40% of the cell’s ATP to pump protons from the cytoplasm to the external environment (Capieaux et al, 1989), which in turn facilitates selective transport of a variety of critical molecules into and out of the cell (Cyert and Philpott, 2013). Pma1 has an unusual property: it is a very long lived protein and continues to accumulate at the plasma membrane over the first several divisions of a mother cell’s life (Thayer et al, 2014). The vacuole pH increase appears to be tied to Pma1 by mass action.…”
Section: The Downside Of Interconnectivity: a Cascade Of Declinementioning
confidence: 99%